2018
DOI: 10.1038/s41467-018-07750-5
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal degradation of NOD2 by NLRP12 in monocytes promotes bacterial tolerance and colonization by enteropathogens

Abstract: Mutations in the nucleotide-binding oligomerization domain protein 12 (NLRP12) cause recurrent episodes of serosal inflammation. Here we show that NLRP12 efficiently sequesters HSP90 and promotes K48-linked ubiquitination and degradation of NOD2 in response to bacterial muramyl dipeptide (MDP). This interaction is mediated by the linker-region proximal to the nucleotide-binding domain of NLRP12. Consequently, the disease-causing NLRP12 R284X mutation fails to repress MDP-induced NF-κB and subsequent activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…Erythrocytes were identified by the high expression of multiple haemoglobin genes ( HBB ). Erythrocytes also expressed immune related genes, such as NACHT, LRR, and PYD domain-containing protein 12 ( NLRP12 ), a potent mitigator of inflammation ( 37 ). Expression of thrombospondin-1 ( THBS1 ), platelet glycoprotein Ib alpha chain ( GP1BA ), and thrombopoietin receptor ( MPL ) genes was used to identify the thrombocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Erythrocytes were identified by the high expression of multiple haemoglobin genes ( HBB ). Erythrocytes also expressed immune related genes, such as NACHT, LRR, and PYD domain-containing protein 12 ( NLRP12 ), a potent mitigator of inflammation ( 37 ). Expression of thrombospondin-1 ( THBS1 ), platelet glycoprotein Ib alpha chain ( GP1BA ), and thrombopoietin receptor ( MPL ) genes was used to identify the thrombocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, SOCS3 negatively regulates NOD2 signaling. Akin to the previous study, Normand et al (53) found that NLRP12 directly interacted with NOD2 through its linker region (residues 200–224). Even if the specific NOD2 region involved in the interaction was not reported, they confirmed that NOD2 was found in complex with the heat-shock chaperon Hsp90.…”
Section: Implications In Our Understanding Of Disease Developmentmentioning
confidence: 56%
“…NLRP12 activation leads to the sequestering of HSP90, which in turn promotes K48-linked ubiquitination and degradation of NOD2 in response to MDP. The significance of NLRP12 as a regulator of NOD2 signaling was highlighted by the finding that LPS-primed NLRP12-deficient mice are highly susceptible to secondary challenge by bacterial MDP (Normand et al, 2018).…”
Section: Activation Of the Nod Pathwaymentioning
confidence: 99%